Kinetics of the Crystalline-Liquid Crystalline Phase Transition of Dimyristoyl L-α-Lecithin Bilayers - Tsong, Tian Yow (Proc Natl Acad Sci U S A, 1974)
Aqueous dispersions of synthetic dimyristoyl L-α-lecithin undergo a sharp decrease in turbidity in the temperature range where the crystalline-liquid crystalline phase transition occurs. Equilibrium transition curves, monitored by the absorbancy change at 300 nm, reproduce all the important features of a calorimetric melting curve [Hinz & Sturtevant (1972) J. Biol. Chem. 247, 6071]. A rapid temperature-jump of the dispersion, measured by the same absorbancy change, has detected several different molecular processes depending on the magnitude of the perturbation. These processes include a phase transition, permeation of ions and water across the membrane, and repture, annealing, or fusion of the bilayer structures. When the temperature-jump is limited to 1 degree, only reactions associated with the phase transition are detectable and no signal is generated after a temperature-jump except for those which end within or extend beyond the transition zones. At least two relaxation times are resolved for the phase transition reactions. The faster one in the millisecond time range is strongly temperature-dependent and has an activation energy close to one million calories per mole. The second one, in the 100-msec time range, appears to have a much smaller activation energy. These observations indicate that strongly cooperative nucleation processes and energy-dependent fast propagation steps occur during the phase transition. Since the kinetics of the transition are complex, intermediate state or transient structures must exist in the transition regions of the bilayer dispersions. These thermal fluctuations of the bilayer structures may have important effects on the lateral diffusion and permeation of molecules and ions in the membrane structure. IMAGES: